2013
DOI: 10.1016/j.polymer.2012.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Highly aligned poly(3,4-ethylene dioxythiophene) (PEDOT) nano- and microscale fibers and tubes

Abstract: This study reports a facile method for the fabrication of aligned Poly(3,4-ethylene dioxythiophene) (PEDOT) fibers and tubes based on electrospinning and oxidative chemical polymerization. Discrete PEDOT nano- and microfibers and nano- and microtubes are difficult to fabricate quickly and reproducibly. We employed poly(lactide-co-glycolide) (PLGA) polymers that were loaded with polymerizable 3,4-ethylene dioxythiophene (EDOT) monomer to create aligned nanofiber assemblies using a rotating glass mandrel during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 32 publications
1
41
1
Order By: Relevance
“…The addition of the MWCNT to the 1:2 scaffolds had no effect on fiber diameter. Feng et al electrospun several 1:10, 3:10, and 5:10 PEDOT:poly(lactide‐ co ‐glycolide) (PLGA) solutions that had average fiber diameters of 10, 3.7, and 2.9 μm, respectively, which are larger than the values we measured. Interestingly, they found that as the amount of PEDOT increased, the fiber diameter decreased; however, we did not observe this effect.…”
Section: Discussioncontrasting
confidence: 70%
“…The addition of the MWCNT to the 1:2 scaffolds had no effect on fiber diameter. Feng et al electrospun several 1:10, 3:10, and 5:10 PEDOT:poly(lactide‐ co ‐glycolide) (PLGA) solutions that had average fiber diameters of 10, 3.7, and 2.9 μm, respectively, which are larger than the values we measured. Interestingly, they found that as the amount of PEDOT increased, the fiber diameter decreased; however, we did not observe this effect.…”
Section: Discussioncontrasting
confidence: 70%
“…Table 1 shows the main peaks registered corresponding to PEDOT undoped (column a) and doped state (column b) at -0.50 V and +0.95 V, respectively [27][28][29][30][31]. Temporal evolution of Raman spectra (Fig 1b) show the characteristic peaks of undoped PEDOT than of doped PEDOT, being the two most intense ones those at 1440 and 1523 cm -1 .…”
Section: Electropolymerization Of 34-ethylendioxythiophene (Edot)mentioning
confidence: 97%
“…Till now, by improved or modified electrospinning technique, nanofibers with part or even good orientation could be fabricated. Martin et al [83] reported the fabrication of aligned PEDOT fibers and tubes based on electrospinning and oxidative chemical polymerization. One-dimensional NCPs fabricated by electrospinning approach exhibit unique electronic and optical properties that can be modified through doping and have wide application in rechargeable batteries, chemical and biological sensors, electromagnetic shielding and wearable electronics, which will be discussed in following sections.…”
Section: Electrospinning Approachmentioning
confidence: 99%